RURAL FINANCE AS A MECHANISM FOR POVERTY ALLEVIATION IN SUDAN, WITH AN EMPHASIS ON „SALAM“ MODE - Khalid M. Mustafa Aburaida (European Scientific Journal, ESJ, 2014)
This paper sheds light on rural finance in Sudan, with an Emphasis on "salam" mode, which recently experienced by banks. As one of the least developed counties, most of people in remote areas in Sudan Suffer from absolute poverty ,although they are capable of producing their necessities to sustain their living, but in most of the cases they lack money. They need capital to reduce the negative effects of unpredictable weather patterns, long crop cycles, irregular market access, and high farm input costs. Recently, after the islamization of the banking system, many islamic modes were adopted like “Morabaha” “Musharka” Modarba” and ”Salam”. The Agricultural Bank of Sudan as the pioneer in serving the agricultural sector in the rurals used to practice successfully "Salam" mode as a suitable mode for small farmers, although it is appeared to be similar to "shail" system .This practice is highly associated with many problems like delay in loan repayments. "In the absence of commercial banks, a large number of non – governmental organizations and other specialized institutions have created financial technologies that serve the increasing number of the poor and sustain loan repayments that are not only competitive with traditional commercial banks , but offer profit without subsidies " . (Hamid, Salih Jibriel, 2006).